ANALISIS YURIDIS TERHADAP PELAKSANAAN REKLAMASI PULAU G JAKARTA UTARA (STUDI PUTUSAN NOMOR: 193/G/LH/2015/PTUN-JKT) - Ivana Novrinda Rambe; Suhaidi Suhaidi; Syamsul Arifin; Sutiarnoto Sutiarnoto (USU LAW JOURNAL, 2018)
ABSTRACT One development which is closely related to living environment is Reclamation. It is a development effort and/ or activity to reclaim land at the river bank or seashore. It is stipulated in the Presidential Regulation No. 122/2012 on Reclamation at the Coastal Areas, the Law No. 27/2007 on the Management of Coastal Areas and Small Islands in conjunction with the Law No. 1/2014 on the Management of Coastal Areas and Small Islands and Article 34 paragraph (1). The reclaimed areas are used for agriculture, housing, industry, shopping center or business, and tourism resorts. This has led reclamation to be permitted. However, there are some problems arising in the establishment license of reclamation; namely the Decree of Governor No. 2238/2014 dated December 23, which is the license for reclamation of Pulau G in Teluk Jakarta. It is resisted by some elements of the society because it has caused them some loss. It resulted in a claim against the ruling to the State Administrative Court in the Decree No.193/G/LH/2015/PTUN-JKT.   Keywords : Reclamation, Environment, G Island North Jakarta.